2022
DOI: 10.3389/fgene.2021.642595
|View full text |Cite
|
Sign up to set email alerts
|

The Pivotal Role of Major Chromosomes of Sub-Genomes A and D in Fiber Quality Traits of Cotton

Abstract: Lack of precise information about the candidate genes involved in a complex quantitative trait is a major obstacle in the cotton fiber quality improvement, and thus, overall genetic gain in conventional phenotypic selection is low. Recent molecular interventions and advancements in genome sequencing have led to the development of high-throughput molecular markers, quantitative trait locus (QTL) fine mapping, and single nucleotide polymorphisms (SNPs). These advanced tools have resolved the existing bottlenecks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 134 publications
0
6
0
Order By: Relevance
“…Furthermore, genome-wide molecular tools (several molecular markers, high-density genetic maps, genotyping strategies, etc.) have also played their role in selecting the best candidate lines and improving plants' genomes [13,14,36]. Recent genomic innovations have accelerated the breeding procedures by modifying the selection methods that are responsible for screening a large amount of data with more precision and efficient breeding (marker-assisted selection, association mapping, breeding by design, genomic selection, gene pyramiding, etc.)…”
Section: Development Of Genomic Technologies and Role In Plant Breedingmentioning
confidence: 99%
“…Furthermore, genome-wide molecular tools (several molecular markers, high-density genetic maps, genotyping strategies, etc.) have also played their role in selecting the best candidate lines and improving plants' genomes [13,14,36]. Recent genomic innovations have accelerated the breeding procedures by modifying the selection methods that are responsible for screening a large amount of data with more precision and efficient breeding (marker-assisted selection, association mapping, breeding by design, genomic selection, gene pyramiding, etc.)…”
Section: Development Of Genomic Technologies and Role In Plant Breedingmentioning
confidence: 99%
“…Cotton is used to make textiles, clothes, medical supplies, and even food products, making it an incredibly versatile crop. Cotton is a vital cash crop for many countries, with production and export of cotton fiber contributing significantly to the GDP of many nations (Razzaq et al, 2022). It is also an important source of employment, providing jobs for millions of people worldwide, from cotton farmers to textile manufacturers.…”
Section: Introductionmentioning
confidence: 99%
“…Cotton fiber quality is an important agronomic trait; therefore, significant efforts have been made to study its biological mechanisms [ 31 , 32 , 33 , 34 , 35 ]. In recent years, several key genes involved in fiber development have been reported [ 36 , 37 , 38 , 39 , 40 ], which have greatly contributed to the study of fiber development mechanisms, and studies have shown that hormones, functional genes, and transcription factors form a complex regulatory network that coordinates the dynamic fiber development process [ 3 ].…”
Section: Introductionmentioning
confidence: 99%